2021
DOI: 10.3390/ijerph18084060
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality in Domestic Environments during Periods Close to Italian COVID-19 Lockdown

Abstract: This paper describes the in situ monitoring of indoor air quality (IAQ) in two dwellings, using low-cost IAQ sensors to provide high-density temporal and spatial data. IAQ measurements were conducted over 2-week periods in the kitchen and bedroom of each home during the winter, spring, and summer seasons, characterized by different outside parameters, that were simultaneously measured. The mean indoor PM2.5 concentrations were about 15 μg m−3 in winter, they dropped to values close to 10 μg m−3 in spring and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…We lack data on indoor air pollution; however, during the lockdown periods some authors found a high indoor-outdoor correlation in Italy due to particle penetration from outside in conjunction with inadequate ventilation. 39 The diagnosis of COVID-19 cases followed the regional indications for being referred to a nasopharyngeal swab which were subject to modifications over time, especially during the first months after the pandemic outbreak. 2 However, we report consistent associations across different pandemic waves.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…We lack data on indoor air pollution; however, during the lockdown periods some authors found a high indoor-outdoor correlation in Italy due to particle penetration from outside in conjunction with inadequate ventilation. 39 The diagnosis of COVID-19 cases followed the regional indications for being referred to a nasopharyngeal swab which were subject to modifications over time, especially during the first months after the pandemic outbreak. 2 However, we report consistent associations across different pandemic waves.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…The interest in studying the impact of COVID-19 in different settings has led to higher scrutiny of the IAQ at homes during the lockdown. A recent study conducted in Northern Italy estimated the average indoor PM 2.5 levels ranged from 8.6 to 18.7 µg/m 3 , which were higher than the outdoor PM 2.5 levels (7.4-15.4 µg/m 3 ) for a two-week study period in summer during the lockdown [4]. In a study conducted in Norway, the IAQ in home offices were evaluated for up to two weeks, and levels of CO 2 and other pollutants higher than health-based standards were detected [50].…”
Section: Discussionmentioning
confidence: 88%
“…The advent of COVID-19 caused the shift of working pattern to work from home remotely for many employees. However, homes may not be a good working environment, compared to conventional office settings with better air conditioning and ventilation systems [4]. In addition, activities performed by individuals at homes may increase indoor air pollution, contributing to more negative health issues [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that indoor particulate matter levels had an almost 3-fold increase in residential settings during and post-lockdown periods [138]. After the imposition of stringent stay-at-home policy, household volatile organic compounds (VOCs) concentrations reached the highest values compared to other periods, as residents spent longer time in their houses while activities outside home were restarted gradually during the re-opening stage [139]. The anthropogenic VOCs emissions-related residential environments during the lockdown may have had an impact on the total ozone formation potential in different areas [140].…”
Section: Substantial Changes Of Ambient and Household Environmental Quality During Covid-19 Lockdownmentioning
confidence: 99%